The Effect of Enforceability - Nunner-Krautgasser Bettina (LeXonomica, 2021)
In this paper, the author focuses on the effect of enforceability, in particular in relation to Austrian law. However, insights into German and European law are also provided. Enforceability is an effect of a judgment which is basically only granted to performance judgments. Declaratory and constitutive decisions (with the exception of the decision on costs) are not enforceable as such. As a result, the order for performance contained in the judgment can be enforced by state coercive measures. Enforceability occurs upon termination of the performance period. Enforceability is neither a consequence of, nor necessarily coincides with, res judicata. The introduction of the Brussels Ia Regulation has fundamentally changed the system of enforcement of foreign decisions. Decisions given in the EU Member State and enforceable in that State are now enforceable in another Member States without the need for a declaration of enforceability. Povzetek. V tem prispevku se avtor osredotoča na učinek izvršljivosti, zlasti v zvezi z avstrijskim pravom. Prav tako pa je podan tudi vpogled v nemško in evropsko pravo. Izvršljivost je učinek sodne odločbe, ki se načeloma priznava le dajatvenim sodnim odločbam. Ugotovitvene in oblikovalne odločbe (razen odločbe o stroških) kot take niso izvršljive. Posledično se lahko odredba o izpolnitvi iz sodne odločbe izvrši z državnimi prisilnimi ukrepi. Izvršljivost nastopi po izteku obdobja izpolnitve. Izvršljivost ni posledica pravnomočnosti niti ni nujno, da sovpada z njo. Uvedba uredbe Bruselj Ia je temeljito spremenila sistem izvrševanja tujih sodnih odločb. Odločbe, izdane v državi članici EU in izvršljive v tej državi, so zdaj izvršljive tudi v drugih državah članicah, ne da bi bilo treba razglasiti njihovo izvršljivost.